2012
DOI: 10.1371/journal.pone.0032101
|View full text |Cite
|
Sign up to set email alerts
|

We Know Too Little about Parasitoid Wasp Distributions to Draw Any Conclusions about Latitudinal Trends in Species Richness, Body Size and Biology

Abstract: Much has been written about latitudinal trends in parasitoid diversity and biology, though it is widely recognised that they are a comparatively poorly known group. Here I show that for both braconid and ichneumonid wasps there are highly significant relationships between body size and the mean recorded latitude of species. Numbers of species per genus (surrogates of clades) peaks in the temperate zone for both families contrasting with data from the virtually complete inventories for mammals, birds and monoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
95
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(98 citation statements)
references
References 36 publications
3
95
0
Order By: Relevance
“…We found that whether diversity was estimated using molecular operational taxonomic units (BINs) or phylogenetic estimates of diversity (PD), there was no significant peak in diversity across latitude. One potential explanation for this is that the rates of under-description outlined by Quicke (2012) are high not only in the tropics but also across latitude. If this were the case, we should expect that estimating latitudinal patterns of diversity within parasitoids would require a massive influx of new samples and sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that whether diversity was estimated using molecular operational taxonomic units (BINs) or phylogenetic estimates of diversity (PD), there was no significant peak in diversity across latitude. One potential explanation for this is that the rates of under-description outlined by Quicke (2012) are high not only in the tropics but also across latitude. If this were the case, we should expect that estimating latitudinal patterns of diversity within parasitoids would require a massive influx of new samples and sites.…”
Section: Discussionmentioning
confidence: 99%
“…However, some have questioned whether this apparent exception is a trend actually caused by limits in taxonomic and geographic sampling (Skillen et al 2000;Willig et al 2003;Jones et al 2009;Baselga et al 2010;Santos and Quicke 2011;Quicke 2012;Veijalainen et al 2012). For example, data from comparatively well-studied northern geographic regions such as North America and Europe (Santos and Quicke 2011) and data gathered over longer time periods may conflate our understanding of species richness (Willig et al 2003).…”
Section: Doubts About Anomalous Diversity Patternsmentioning
confidence: 99%
“…Both ichneumonid wasps (which are parasitoids of insects [Owen and Owen 1974]) and aphids (which are pathogens on plants) (Dixon et al 1987), also appear to be less diverse in the tropics (but see Quicke [2012] who questions this pattern for ichneumonids). The ''resource fragmentation hypothesis'' has been proposed to explain these ''reversed'' patterns (Kindlmann et al 2007).…”
Section: Using Parasite Ldgs To Inform General Principlesmentioning
confidence: 99%
“…Furthermore, absence of evidence cannot be considered as evidence for absence, especially in the case of parasitoid wasp distributions in regions as understudied as the Old World and New World tropics (Quicke 2012). Current distribution records might thus give a drastic underestimation of the actual distribution of the genus, and Dimophora might have a much larger distribution than currently recognized.…”
Section: Discussionmentioning
confidence: 98%